Pendampingan Penggunaan Sistem Informasi Akademik (SIAKAD) dalam Mendukung Digitalisasi Layanan Akademik di STIT Aqidah Usymuni Sumenep - Moh. Zainol Kamal; Ahmad Effendi; Nufil Indriyani (LP3M IAIFA Kediri, 2026)
This mentoring activity aims to provide understanding and skills to the academic community in using SIAKAD effectively through mentoring activities. The activity implementation method uses a participatory approach through several stages, namely needs analysis, program planning, mentoring implementation, monitoring and evaluation, as well as reflection and follow up. Mentoring activities are carried out through training, system demonstrations, direct practice, and technical consultations related to SIAKAD operations. The materials provided include student data management, filling out KRS, managing lecture schedules, inputting grades, and utilizing system features to support digital-based academic services. Monitoring and evaluation are carried out to measure the level of understanding and skills of participants in operating the system and to determine the effectiveness of the mentoring activities that have been implemented. The results of the activity indicate that mentoring in the use of SIAKAD is able to improve the understanding and skills of the academic community in utilizing the academic information system more optimally. The academic community demonstrated an increased ability to manage academic data digitally and understand the various features available in the system. This activity also contributes to encouraging the digitalization of academic services that are more effective, efficient, and transparent within the STIT Aqidah Usymuni Sumenep environment.